Arquitectura, un camino en contribución y fortalecimiento del desarrollo cultural en el municipio de Palmira. - Florez Acevedo, Sebastian (Universidad Antonio Nariño, 2024)
owadays architecture with its new trends is starting to become more and more unattainable and difficult to recreate for less developed countries. The current architecture in less developed countries faces challenges and limitations that may hinder the creation of monuments of the new trends.